Does Tax Effort Moderate the Effect of Government Expenditure on Regional Economic Growth? A Dynamic Panel Data Evidence from Indonesia - Amri, Khairul; Masbar, Raja; Nazamuddin, B. S.; Aimon, Hasdi (Ekonomika, 2023)
Our research study aims to analyze the effect of government expenditure on goods and services and capital toward regional economic growth in Indonesia. We position local tax effort as a moderating variable between economic growth and government expenditures. Using a panel data set of 24 provinces in Indonesia from 2006 to 2015, a dynamic model of GMM was applied to estimate the effect of public expenditure on growth. The research study provides empirical evidence that the two kinds of public spending positively and significantly affect economic growth. Conversely, local tax efforts negatively affect economic growth. Besides, local tax efforts also reduce the positive impact of capital expenditure on economic growth. In other words, local tax efforts negatively moderate the influence of government expenditure on the output growth of the regional economy.
Keywords: Economic growth; local tax effort; government expenditure; GMM estimation